If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=6/c-2
We move all terms to the left:
2-(6/c-2)=0
Domain of the equation: c-2)!=0We get rid of parentheses
c∈R
-6/c+2+2=0
We multiply all the terms by the denominator
2*c+2*c-6=0
We add all the numbers together, and all the variables
4c-6=0
We move all terms containing c to the left, all other terms to the right
4c=6
c=6/4
c=1+1/2
| 2.3=0.15(2y-3)-6 | | 5(2b3)=2b+9 | | 50/g=10 | | 22-4b=18 | | -1.1=-4x/3+3/2 | | 65+x=130 | | 10/u+36=38 | | 61=19+6h | | 7y-36=41 | | -1.1=-4x+3/2 | | 3(2v+8)=54 | | 5/x-90=100 | | -1.1=4x+3/2 | | -3z=-11/3 | | x+3x-17=87 | | 4(x+3)-7=5x | | 5*x+6=8 | | 5.x+6=8 | | 145=z25145=z25 | | |y+2|+5=8 | | -22/3-3z=0 | | 5+3x=-26 | | 3z=-22/3 | | 58.x-6=147 | | x+(2x)=180 | | (180-x=x | | 8(x-1)=7x-14 | | 3x+6=50+x | | -36=4x=16 | | 8x=60-3x | | t(0.1t-2)=30 | | 4(2x+6)-5x=61 |